Crystal Structure of Monomeric Photosystem II from Thermosynechococcus elongatus at 3.6-Å Resolution - Broser, Matthias (American Society for Biochemistry and Molecular Biology, 2010)
The membrane-embedded photosystem II core complex (PSIIcc) uses light energy to oxidize water in photosynthesis. Information about the spatial structure of PSIIcc obtained from x-ray crystallography was so far derived from homodimeric PSIIcc of thermophilic cyanobacteria. Here, we report the first crystallization and structural analysis of the monomeric form of PSIIcc with high oxygen evolution capacity, isolated from Thermosynechococcus elongatus. The crystals belong to the space group C222(1), contain one monomer per asymmetric unit, and diffract to a resolution of 3.6 Å. The x-ray diffraction pattern of the PSIIcc-monomer crystals exhibit less anisotropy (dependence of resolution on crystal orientation) compared with crystals of dimeric PSIIcc, and the packing of the molecules within the unit cell is different. In the monomer, 19 protein subunits, 35 chlorophylls, two pheophytins, the non-heme iron, the primary plastoquinone Q(A), two heme groups, 11 β-carotenes, 22 lipids, seven detergent molecules, and the Mn(4)Ca cluster of the water oxidizing complex could be assigned analogous to the dimer. Based on the new structural information, the roles of lipids and protein subunits in dimer formation of PSIIcc are discussed. Due to the lack of non-crystallographic symmetry and the orientation of the membrane normal of PSIIcc perpendicular (∼87°) to the crystallographic b-axis, further information about the structure of the Mn(4)Ca cluster is expected to become available from orientation-dependent spectroscopy on this new crystal form.